2021
DOI: 10.1029/2021jb021826
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Prediction With Uncertainty Quantification From Multiple Seismic Attributes Using Random Forest

Abstract: Porosity is one of the most critical parameters for subsurface characterization, and is of vital interest to understand fluid flow properties (Bernabé, 1995;Carman, 1956), elastic and mechanics behaviors of rocks (McBeck et al., 2019), and pore pressure evolution and prediction (Obradors-Prats et al., 2017). Therefore, predicting porosity from seismic data has significant influences in geo-energy (oil, gas, geothermal, etc.) reservoir characterization and development (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…In terms of model uncertainty, it could be inferred from Figure that the MLM has the lowest uncertainty. Herein, we evaluate the uncertainty as described elsewhere, , in terms of R 2 and RMSE. A high R 2 and a low RMSE generally indicate greater confidence in model predictions.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of model uncertainty, it could be inferred from Figure that the MLM has the lowest uncertainty. Herein, we evaluate the uncertainty as described elsewhere, , in terms of R 2 and RMSE. A high R 2 and a low RMSE generally indicate greater confidence in model predictions.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the approach could help highlight interesting geological and hydrocarbon characteristics and improve traditional seismic interpretation techniques. Likewise, [19] used the Random Forest algorithm to deduce porosity from a number of seismic attributes, and the results proved the effectiveness of ML to characterize spatially varying porosity in a reservoir rock with quantification of the uncertainty. Reference [20] proposed applying DL to predict lithofacies from seismic data and found that the approach improved resolution in the presence of complex geological environments.…”
Section: Introductionmentioning
confidence: 88%
“…Most studies in this category design deep neural networks that are capable to capture the complex transformation from the measured data space to the desired model parameter space, train these machines using paired models and their corresponding synthetic data, and apply the trained machines to field datasets. Applications of such a framework range across the whole spectrum of geophysical inverse problems, including surface wave dispersion inversion and tomography (Cai et al., 2022; X. Zhang & Curtis, 2021), seismic‐to‐petrophysics inversion (Xiong et al., 2021; C. Zou et al., 2021), crustal thickness and Vp / Vs estimation from receiver functions (F. Wang et al., 2022), earthquake and microseismicity moment tensor inversion (Chen et al., 2022; Steinberg et al., 2021), magnetic, gravity, and ground‐penetrating radar (GPR) data inversion (R. Huang et al., 2021; Leong & Zhu, 2021; Nurindrawati & Sun, 2020), and thermal evolution estimation for Mars (Agarwal et al., 2021). Y. Wu et al.…”
Section: Highlightsmentioning
confidence: 99%
“…Applications of such a framework range across the whole spectrum of geophysical inverse problems, including surface wave dispersion inversion and tomography (Cai et al, 2022;X. Zhang & Curtis, 2021), seismic-to-petrophysics inversion (Xiong et al, 2021;C. Zou et al, 2021), crustal thickness and Vp/Vs estimation from receiver functions (F. Wang et al, 2022), earthquake and microseismicity moment tensor inversion (Chen et al, 2022;Steinberg et al, 2021), magnetic, gravity, and ground-penetrating radar (GPR) data inversion (R. Leong & Zhu, 2021;Nurindrawati & Sun, 2020), and thermal evolution estimation for Mars (Agarwal et al, 2021).…”
Section: Geophysical Inversionmentioning
confidence: 99%